Institutional options for managing rangelands - CGIAR Program on Collective Action and Property Rights (International Food Policy Research Institute, 2010)
Rangelands occupy nearly one-half of the Earth's land area or around 16 billion acres. About one-half of this area is used for grazing livestock. Rangelands have been subject to a wide range of tenure arrangements, with different structures for regulating access to, use of, and management of rangelands. These include many customary and tribal institutional arrangements that have functioned for long periods. Each of these property rights regimes and institutional options is associated with different costs for achieving various goals, such as poverty reduction, equitable access to resources, and sustainable use and management of those resources. The benefits and costs of alternative tenure and institutional arrangements and the impact of existing legal and policy frameworks on the sustainability and equity of pastoral production systems vary depending on the category of land ownership: state ownership; individual ownership; or common property